Translating Knowledge(s) across Time and Space: Audiovisual Translation of “Traditional Chinese Medicine and Culture” Open Course (a Case Study) - Zou, Yuan; Blumczynski, Piotr (Journal of Audiovisual Translation, 2025)
The audiovisual translation (AVT) of online courses plays a crucial role in the rapidly evolving global education landscape. This means that Massive Open Online Courses become massive translation sites, in which complex linguistic, cultural, and epistemological challenges are negotiated. Taking a cue from the EPISTRAN international research project, this article takes a close look at a hugely popular MOOC devoted to Traditional Chinese Medicine and Culture to identify both challenges as well as elements of good practice. One of the key findings is that integrating a translational perspective early into the design process, rather than viewing translation as an extra linguistic layer added at the end, helps minimise conceptual mismatches, maximise participant engagement, and encourage constant revision and updating of knowledge. MOOCs offered by world-renowned educational institutions to a broad range of multilingual and multicultural audiences powerfully showcase translation in its knowledge-making role. Lay summary This paper explores translating specialized knowledge across time and space, specifically through a case study on the AVT in a TCM MOOC. As discussed in the introduction, knowledge emerges, grows, and develops in a specific linguistic, cultural, intellectual, social, political, religious, geographic, and historical context, making it inherently situated. The paper aims to demonstrate how the translation of knowledge involves negotiation of time and space, how knowledge is adapted for international audiences, and what challenges and good practice may be identified by examining the translation of epistemologically and culturally complex content. Taking translating TCM from ancient China to the modern Western world as a case study, this paper has highlighted barriers such as philosophical differences, conceptual mismatches, linguistic and cultural diversity, and technical issues in translating the knowledge for international learners. One of the key findings is that integrating a translational perspective early into the design process – rather than viewing translation as an extra linguistic layer added at the end – helps to mitigate the above challenges. In this MOOC, we identified some effective practices for translating knowledge like reframing complex ideas, engaging learners interactively, and updating the content with the development of knowledge. This study also showed that translation evolves over time through interactions with other cultures and in line with the growth of understanding. As AVT and MOOCs continue to expand globally, these insights emphasize the need for ongoing innovation in translation to reach diverse audiences, creating a bridge that connects knowledge(s) across time and space and fosters a truly global exchange of ideas.